Biofertilizer Formulation in Stimulating Corn Growth in Drought Stress Peatland - Santa Maria Lumbantoruan; Selviana Anggraini (University of Prof. Dr. Hazairin, SH, 2021)
The area of peatland has the potential to be used as agricultural land, but the potential of this peatland has challenges that are not easy to manage in a sustainable manner. Improper management can cause peat soils to experience drought stress. A technological approach that can be used to optimize the use of peat soils experiencing drought stress in maize can be done by applying a biofertilizer formulation. The purpose of this study was to obtain a biofertilizer formulation to increase the growth and production of maize under drought stress conditions on peat soil. This research was conducted in the experimental garden of Bina Insan University, Lubuk Linggau The design used in this study was a completely randomized block design with 2 treatment factors, namely the first treatment factor for biological fertilizers, namely H0: without Mycorrhizae, H1: Mycorrhizae + Petrobio, H2: Mycorrhizae + Agrozeabiochar, H3: Mycorrhizae + Pugam. The second treatment factor was the intensity of watering, namely P1: Watering once a day, P2: Watering once in 3 days, P3: Watering once in 5 days, P4: Watering once in 7 days. The treatment factor was repeated 4 times to obtain 64 plants. The results of the study on the application of biofertilizer formulations after being analyzed at the 5% level showed significantly different results in plant height, root dry weight. Biofertilizer formulations that can increase the resistance of maize plants on peat soils under drought stress were shown by the treatment of the biological fertilizer formulations Micorrhiza + petrobio (H1) and Mycorrhiza + pugam (H3).